Evaluation of Medium and Large-Scale Mushroom Companies in Turkey - Erkan Eren; Gölgen Bahar Öztekin; Yüksel Tüzel (Turkish Journal of Agriculture: Food Science and Technology)
The commercial production of cultivated-mushroom, which has a forty years of past in Turkey, was started after 1980s. Until the recent decade, most of the total amount of production in Turkey was performed by family members while the cultivation of the product has gained an upward trend since the beginning of 2000s, though the amount and development rate were not enough. During that time, a number of large (>2000 m2) and medium (500-2000 m2) scale mushroom production facilities were established and Turkey has gained an important place in mushroom production in the world. In this study, we aimed to reveal the common production methods of ten medium and large scale mushroom companies whose daily production capacities are above 1 ton in six regions. In this respect, all companies have been visited and communicated directly with company representatives and a survey comprising 65 questions about company, production facility, compost and casing soil, production systems, diseases and pests and packaging was made. The findings have suggested us that such companies have mostly a history of 15 years of time and have a land size of 10-50 thousand m2, while their mushroom production areas vary between in size and that they make use of technology in production and automation in their plants and they have quality management systems (ITU, ISO 9001, ISO 22000 and Global Gap ) and they employ generally qualified and experienced technicians or agriculture engineers and also that 40% of them receive consultancy and also that they use their own productions or standard ready mycelium planted compost and that they use domestic peat as casing material and that they package the mushrooms with their brands and sell to markets mostly and lastly that they conduct pre-sale quality sorting and grading. It was also seen that there is lack of food engineers employed and most of the companies do not receive consultancy, and that the waste compost is not evaluated correctly and that the covering material is not in the required standards and that there are even companies not doing any water analysis and that coal for heating and chemicals for disinfection are used and that diseases and pests are inevitable and last that they lack in processing different products.